Tachinidae (Diptera) reared from clearwing moths (Lepidoptera: Sesiidae) in Slovenia - Predovnik, Željko (Acta entomologica slovenica (Ljubljana), 2007)
Host data are given for four Tachinidae (Diptera) species which are recorded for Slovenia for the first time: Bithia demotica (Egger, 1861), B. glirina (Rondani, 1861), B. proletaria (Egger, 1860) and Leskia aurea (Fallén, 1820). Bembecia megillaeformis (Hübner, 1813) and Pyropteron (Pyropteron) chrysidiformis (Esper, 1782) or Pyropteron (Synansphecia) triannuliformis (Freyer, 1845) are first host records for Bithia proletaria. The following hosts are new records for the respective tachinids: Bembecia ichneumoniformis (Denis & Schiffermüller, 1775) and Pyropteron (Synansphecia) affinis (Staudinger, 1856) for Bithia demotica; Synanthedon melliniformis (Laspeyres, 1801) and Synanthedon loranthi (Králíček, 1966) for Leskia aurea.
Keywords: Diptera; entomologija; favna; muhe goseničarke; parazitoidi; Slovenia; Slovenija